1995
DOI: 10.1021/jm00008a007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Histamine H1 Receptor Agonist Activity of a Series of 2-Phenylhistamines, 2-Heteroarylhistamines, and Analogs

Abstract: New histamine derivatives characterized by a (substituted) aryl, heteroaryl, benzyl, or heteroarylmethyl substituent in the C2 position of the imidazole ring have been prepared from appropriate imidates or amidines, respectively, and 2-oxo-4-phthalimido-1-butyl acetate (1). The compounds were screened as potential H1 receptor agonists on the isolated guinea pig ileum. The 3-halogenated 2-phenylhistamines (halogen = Br (35) and I (36)) were equipotent with histamine, while 2-(3-(trifluoromethyl)phenyl)histamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 23 publications
2
57
0
1
Order By: Relevance
“…7C). For the phenylhistamines, the efficacies are either in the same range at both hH 1 R and hH 4 R or higher at hH 1 R that at hH 4 R. Collectively, 2-phenylhistamines are less selective H 1 R agonists than originally assumed (Leschke et al, 1995;Seifert et al, 2003). Future studies will have to determine whether the previously reported H 1 R and H 2 R antagonist-resistant effects of 2-phenylhistamines in HL-60 leukemia cells are mediated by hH 4 R rather than by the originally assumed receptor-independent direct G-protein activation (Seifert et al, 1994).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…7C). For the phenylhistamines, the efficacies are either in the same range at both hH 1 R and hH 4 R or higher at hH 1 R that at hH 4 R. Collectively, 2-phenylhistamines are less selective H 1 R agonists than originally assumed (Leschke et al, 1995;Seifert et al, 2003). Future studies will have to determine whether the previously reported H 1 R and H 2 R antagonist-resistant effects of 2-phenylhistamines in HL-60 leukemia cells are mediated by hH 4 R rather than by the originally assumed receptor-independent direct G-protein activation (Seifert et al, 1994).…”
Section: Discussionmentioning
confidence: 77%
“…We included structurally diverse H 1 R antagonists of the first and second generation as well as antidepressants, acting also as H 1 R antagonists, into our study (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Moreover, we characterized small H 1 R agonists (19)(20)(21)(22)(23)(24) and H 1 R agonists of the phenylhistamine (25-36) and histaprodifen (37-41) classes (Leschke et al, 1995;Kramer et al, 1998;Elz et al, 2000;Menghin et al, 2003) at hH 4 R.…”
mentioning
confidence: 99%
“…2-Methylhistamine (2) and 2-(2-thiazolyl)ethanamine (3) were synthesized using standard procedures. Compounds 5 to 18 were prepared according to published procedures (Zingel et al, 1990;Leschke et al, 1995). Compounds 22, 23, and 40 were available by synthetic pathways reported for the synthesis of 19 to 21 (Elz et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Neomycin has been reported to inhibit hormone-stimulated IP 3 production through the blockade of PLC (Phillippe, 1994). The administration of U-73122 and neomycin dose-dependently prevented the hypernociception induced by 2-(3-trifluoromethylphenyl)-histamine (FMPH), a new, potent and selective H 1 -receptor agonist (Leschke et al, 1995). By contrast, U-73343, a succinimido analogue used as negative control for U-73122 being a weak inhibitor of PLC Smith et al, 1990), did not modify the hyperalgesia induced by FMPH.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to determine whether the stimulatory effect of H 1 -receptor agonists on PLC, and on DAG-and IP 3 -mediated intracellular pathways, participates in the mechanism of central hypernociception following activation of the H 1 -mediated histaminergic system. To this purpose, 2-(3-trifluoromethylphenyl)histamine (FMPH), a new, potent and selective H 1 -receptor agonist (Leschke et al, 1995) was employed.…”
Section: Introductionmentioning
confidence: 99%